Plasma Levels of Myocardial MicroRNA-133a Increase by Intraoperative Cytokine Hemoadsorption in the Complex Cardiovascular Operation - Wagner, Robert; Soucek, Premysl; Ondrasek, Jiri; Fila, Petr; Sterba, Jan; Spacilova, Hana; Michalcikova, Alzbeta; Freiberger, Tomas; Nemec, Petr (Journal of clinical medicine research, 2019)
BACKGROUND: Complex cardiovascular procedures may initiate a systemic inflammatory response syndrome (SIRS) with a massive cytokine release, which is involved in postoperative myocardial injury. Intraoperative cytokine hemoadsorption (HA) mitigates the inflammatory response. Micro ribonucleic acids (miRNAs) are emerging as a marker of myocardial injury. METHODS: This study evaluated if intraoperative cytokine reduction by HA modulates SIRS and affects myocardial injury as measured by miRNA-126, 223 and miRNA-1, 133a, respectively. Twenty-eight patients were assigned into HA (n = 15) and control (C) (n = 13) groups. HA was performed by integrating CytoSorb™ into the extracorporeal circuit. RESULTS: MiRNA-133a plasma levels were increased postoperatively in both groups but were much higher in the HA group than in the C group at 3 h (P = 0.037) and 18 h (P = 0.017) after reperfusion. MiRNA-1 and miRNA-223 plasma levels were significantly increased postoperatively, but did not differ between groups. The vascular miRNA-126 was not affected. CONCLUSION: Intraoperative cytokine HA in cardiovascular operations increased the plasma levels of miRNA-133a, suggesting higher myocardial injury.
Keywords: Cardiac operations; MicroRNA; Myocardial injury; Cytokines; Hemoadsorption; Systemic inflammatory response syndrome